Pengaruh Baling – Baling Terhadap Kerugian Tekanan Aliran Udara Di Dalam Pipa - Prawono, Sigit Ari; Qiram, ikhwanul; Mukhtar, Anas (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2018)
This study aims to minimize the occurrence of air pressure losses in the airflow pipe. The research was carried out by giving the blades varying 5, 6, 7 blades with an angle of 40˚, 50˚, 60˚ in the pipe with full valve, valve openings, ½ and ¼, measurements were made at 3 measurement points using a manometer U in place it in the pipe before passing the propeller and after passing the propeller there are 2 measurement points. The results showed that the smaller the number of blades with the smallest angle, the greater the pressure produced, and the more the number of blades with the largest angle, the smaller the pressure produced